Pertumbuhan dan Hasil Rimpang Jahe Merah (Zingiber officinale, Rosc.) Varietas Jahira 1 dengan Pemberian Arang Sekam: Growth and Yield of Red Ginger Rhizome (Zingiber officinale, Rosc.) Variety Jahira 1 with The Application of Husk Charcoal - Windu Mangiring; Maman; Adwin Pangestu (Planta Simbiosa, 2023)
This research aims to assess the impact of rice husk charcoal application on the growth and yield, as well as to determine the optimal dosage of rice husk charcoal for enhancing the growth and yield of red ginger rhizomes (Zingiber officinale, Rosc.) variety Jahira 1. The experiment was conducted in Ciruluk Village, Kalijati District, Subang Regency, from June to September 2022. The study utilized an experimental method with a randomized block design consisting of four replications and six treatments of rice husk charcoal dosage. The treatments included: P0 = 0 ton/ha, P1 = 2.5 ton/ha, P2 = 5 ton/ha, P3 = 7.5 ton/ha, P4 = 10 ton/ha, and P5 = 12.5 ton/ha. The results of the study indicate that the application of rice husk charcoal significantly affects the growth of red ginger plants (Zingiber officinale, Rosc.) variety Jahira 1. The dosage of 10 ton/ha of rice husk charcoal resulted in the tallest plants at the observation of 4 weeks after planting (WAP), while doses of 5 and 7.5 ton/ha provided the best results at 8 WAP. Treatments P2 (5 ton/ha), P3 (7.5 ton/ha), P4 (10 ton/ha), and P5 (12.5 ton/ha) yielded the best results at 12 WAP. The application of rice husk charcoal also influenced the leaf count, where the dosage of 5 ton/ha (P2) yielded the best results at 4 WAP, while doses of 5 and 7.5 ton/ha (P2 and P3) provided the best results at 8 WAP. The application of 7.5 ton/ha (P3) resulted in the highest number of shoots at 12 WAP. The application of rice husk charcoal did not have a significant effect on leaf length, rhizome weight per plant, and rhizome weight per plot.